(3GdEYLGR hGdEjLGRs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s ((3CMeO Hf eMeO Hf YHO GdZfi GdeYQha HGHf GdQHjH s)
(3ChdgG (B:s
(3bGd CHh efUhQ CeG HYO MeOkG ddg YR GSeg aef GdcHGFQ Cf JSjQ eDdaGJi ai GdHdG eSjQ GdCeKGd hJSQi eQi GdNjGd GdHGH GdChd ai HYV eG fWb Hg GdbQBf ef GjLGR GdeYLRGJ s
(3BNQgG (B:s
(3YQac Gddg ef HQcGJg eG jQi Ydi YOO GdUGFejf hGdaGFejf aGFRG HGdeKhHI ef GdNGdb hGdTcQ ef GdNGdbjf s
(3GdfSNI HgG MhGTs
(3HChdg eWGdYI hJedcGJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs